APPLICATION OF COMMUNICATION SERVICES OF LIBRARY SERVICES IN IMPROVING COMMUNITY READING LOVE CULTURE - Har Yati (Fakultas Ilmu Sosial dan Ilmu Politik, 2023)
Regional public libraries have a very important role to foster the development of reading and increase information literacy in the community. The government has always viewed the library development as sporadic. And there are still many who do not meet the National Library Standards. Based on Law Number 43 of 2007 concerning the National Library Standards Article 32, one of them reads